Inflation and Wealth Distribution - Burkhard Heer; Bernd Süssmuth (Center for Economic Studies and ifo Institute (CESifo), 2003)
The effect of a permanent change of inflation on the distribution of wealth is analyzed in a general equilibrium OLG model that is calibrated with regard to the characteristics of the US economy. Poor agents accumulate savings predominantly in the form of money, while rich agents participate in the stock market and accumulate equity. Surprisingly, an increase of inflation results in a lower stock market participation rate; in addition, the distribution of wealth becomes more unequal, even though the quantitative effect is economically negligible. Furthermore, we show that the welfare costs of anticipated inflation are considerably lower than in Imrohoroglu (1992).
Keywords: 330; inflation; welfare costs; wealth distribution; stock market participation